Pelatihan Kiat-Kiat Menambah Pendapatan Rumah Tangga - Gultom, Robinhot; Sinaga, Anton A. P.; Sihite, Mislan; Silalahi, Sahat P. Remus; Normi, Siti; Melianna, Saur; Rajagukguk, Tiur; Marbun, Sondang Ni Bulan; Siregar, Selamat; Panggabean, Toman; Saragih, Rintan; Sitohang, Rommel (Universitas Methodist Indonesia, 2024)
Lingkungan VIII, Babura Village, Medan Baru District consists of six sub-districts in Medan Baru District. Lingkungan VIII is one of the wards in Babura Village out of 13 wards in this subdistrict. The Community Service Team (PKM) provides enlightenment to mothers in order to increase their income. In general, mothers in the neighborhood live at home and therefore the PKM Team provides a way to increase their income. The aim of this PKM is to train mothers to do business or entrepreneurship and motivate mothers to become entrepreneurs. Mothers are expected to have creative ideas by being able to process various preparations using cheap basic ingredients, such as bananas, cassava and the modern cake business. The results of this processing are used as an idea to be used as an opportunity for entrepreneurship to increase household income.